Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To determine the equation that represents the direct variation between [tex]\( a \)[/tex] and [tex]\( b \)[/tex], we need to understand the relationship described in the problem.
We are given that [tex]\( b \)[/tex] is located the same distance from 0 as [tex]\( a \)[/tex], but in the opposite direction. This relationship can be described mathematically as [tex]\( b \)[/tex] being the negative of [tex]\( a \)[/tex].
Consider the given example: when [tex]\( a = -2.75 \)[/tex], we have [tex]\( b = 2.75 \)[/tex].
Let's analyze each potential equation one by one to check which one fits this description:
1. [tex]\( b = -a \)[/tex]:
- If [tex]\( a = -2.75 \)[/tex], then [tex]\( b = -(-2.75) = 2.75 \)[/tex].
- This is true for the example given.
2. [tex]\( -b = -a \)[/tex]:
- If [tex]\( a = -2.75 \)[/tex], then [tex]\( -b = -(-2.75) = 2.75 \)[/tex].
- This simplifies to [tex]\( b = -2.75 \)[/tex], which is incorrect for the given example.
3. [tex]\( b - a = 0 \)[/tex]:
- If [tex]\( a = -2.75 \)[/tex], then [tex]\( b - (-2.75) = 0 \)[/tex].
- This simplifies to [tex]\( b + 2.75 = 0 \)[/tex], or [tex]\( b = -2.75 \)[/tex], which is incorrect for the given example.
4. [tex]\( b(-a) = 0 \)[/tex]:
- This equation implies that either [tex]\( b = 0 \)[/tex] or [tex]\( -a = 0 \)[/tex], neither of which are true for the given values (since [tex]\( a = -2.75 \)[/tex] and [tex]\( b = 2.75 \)[/tex]).
- Thus, this equation does not fit the relationship described.
Based on the analysis, the correct equation that represents the direct variation between [tex]\( a \)[/tex] and [tex]\( b \)[/tex] is:
[tex]\[ b = -a \][/tex]
So, the correct answer is:
[tex]\[ b = -a \][/tex]
We are given that [tex]\( b \)[/tex] is located the same distance from 0 as [tex]\( a \)[/tex], but in the opposite direction. This relationship can be described mathematically as [tex]\( b \)[/tex] being the negative of [tex]\( a \)[/tex].
Consider the given example: when [tex]\( a = -2.75 \)[/tex], we have [tex]\( b = 2.75 \)[/tex].
Let's analyze each potential equation one by one to check which one fits this description:
1. [tex]\( b = -a \)[/tex]:
- If [tex]\( a = -2.75 \)[/tex], then [tex]\( b = -(-2.75) = 2.75 \)[/tex].
- This is true for the example given.
2. [tex]\( -b = -a \)[/tex]:
- If [tex]\( a = -2.75 \)[/tex], then [tex]\( -b = -(-2.75) = 2.75 \)[/tex].
- This simplifies to [tex]\( b = -2.75 \)[/tex], which is incorrect for the given example.
3. [tex]\( b - a = 0 \)[/tex]:
- If [tex]\( a = -2.75 \)[/tex], then [tex]\( b - (-2.75) = 0 \)[/tex].
- This simplifies to [tex]\( b + 2.75 = 0 \)[/tex], or [tex]\( b = -2.75 \)[/tex], which is incorrect for the given example.
4. [tex]\( b(-a) = 0 \)[/tex]:
- This equation implies that either [tex]\( b = 0 \)[/tex] or [tex]\( -a = 0 \)[/tex], neither of which are true for the given values (since [tex]\( a = -2.75 \)[/tex] and [tex]\( b = 2.75 \)[/tex]).
- Thus, this equation does not fit the relationship described.
Based on the analysis, the correct equation that represents the direct variation between [tex]\( a \)[/tex] and [tex]\( b \)[/tex] is:
[tex]\[ b = -a \][/tex]
So, the correct answer is:
[tex]\[ b = -a \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.